Geléia light elaborada artesanalmente a partir do resíduo da filtração do suco de laranja - Petry, Fernanda Tais Souza (2011)
This paper had for aim, making use of the production industry waste of whole orange juice, to draw light orange jam considering alternative and convencional grow and different sucralose concentration, 15%, 20% and 30%. It was considered the physicochemical characteristics and light standards, red and yellow color of the juice, pulp and jelly orange light obtained from alternative and conventional grow. It was done analysis for microbiological and sensory jelly in order to establish the best formulation. The treatments were established: jelly produced with conventional orange juice, jelly pulp obtained from conventional orange, jelly produced with alternative orange juice and jelly made with orange pulp from alternative cultivation. Each one of the treatment had four experiments: a control group produced with sugar and the others varying the concentrations of sucralose, using in this case, 15%, 20% and 30%. For the analysis of soluble solids, as much juice as the orange pulp when considering the different grow, showed no significant difference at 5% level, contrary to findings of acidity, pH and ° Brix / acidity. The juice and pulp either conventional or alternative grow showed a significant difference at 5% level for the parameters of brightness, red (+ a) and yellow (+ b). The sample of alternative orange juice showed higher brightness and yellow, whereas red the highest value was found for the sample of conventional orange pulp. The physicochemical analysis for jelly made with juice as the control group as for those made with sucralose, showed average values for reducing sugar content between 8.133 to 11.03, for the acidity range 0.8 to 1.71, pH soluble solids total the minimum and maximum average were 3.36 to 3.82 and 69.75 to 27.25 respectively. For the jellies made with pulp, alternative grow and sugar showed levels L * and b *, higher compared with other experiments, to values of a * also was the sample in the control group which showed the greatest value, however the raw material was conventional grow. Microbiological analysis to counting of yeasts and molds showed a sample over the limits set down in law and to counting of mesophilic samples showed contamination, all of them made with 30% of sucralose. The formulation determined as favorite was the jelly made with orange pulp from the conventional grow and 15% sweetener, sucralose. The acceptance of products made of sucralose, lets enable the production of light-based industrial waste, adding value and meeting the market demands. It demonstrates that the analysis done showed significant differences as variables of grow as for raw materials and concentrations of sucralose and can not be established correlation between variables.